Microstructural modelling of nuclear graphite using multi-phase models - Berre, C; Fok, S; Marsden, B; Mummery, P; Marrow, T; Neighbour, G (2008)
This paper presents a new modelling technique using three-dimensional multi-phase finite element models in which meshes representing the microstructure of thermally oxidised nuclear graphite were generated from X-ray micro-tomography images. The density of the material was related to the image greyscale using Beer-Lambert's law, and multiple phases could thus be defined. The local elastic and non-linear properties of each phase were defined as a function of density and changes in Young's modulus, tensile and compressive strength with thermal oxidation were calculated. Numerical predictions compared well with experimental data and with other numerical results obtained using two-phase models. These models were found to be more representative of the actual microstructure of the scanned material than two-phase models and, possibly because of pore closure occurring during compression, compressive tests were also predicted to be less sensitive to the microstructure geometry than tensile tests. © 2008 Elsevier B.V. All rights reserved.